THE IMPORTANT ROLE OF WORK-LIFE BALANCE AND JOB INSECURITY IN EMPLOYEE JOB SATISFACTION TO REDUCE TURNOVER INTENTION - Wachyu Hari Haji; Zulhawati; Ariani, Meiliyah; Islamiah Kamil (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
Turnover intention is something that is avoided by a company, because the turnover phenomenon has a negative impact on every company. This study aims to determine the important role of work-life balance and job insecurity in employee job satisfaction to reduce turnover intention at PT Bhinneka Cipta Lestari in West Jakarta. The type of data in this study is quantitative data. The source used is primary data. The population and sample in this study are all employees who work at PT Bhinneka Cipta Lestari in West Jakarta with a total of 71 employees. This study uses a saturated sampling technique, where the entire population is used as a research sample. The sampling technique used for sampling is non-probability. The data collection method uses a questionnaire that aims to find out the opinions of respondents regarding the important role of work-life balance and job insecurity in employee job satisfaction to reduce turnover intention. The data analysis in this study used multiple linear regression using validity test, reliability test, multiple linear regression analysis test and t hypothesis test and determination coefficient test with the SPSS 27 For Windows statistical application program. The results showed that partially work-life balance had a negative and insignificant effect on turnover intention, job insecurity had a negative and insignificant effect on turnover intention, and job satisfaction had a significant positive effect on employee turnover intention. It is important for companies to always implement work-life balance and provide a sense of security at work so that it creates a sense of satisfaction in employees. This can certainly minimize the occurrence of turnover intention.